QTL mapping for resistance to and tolerance for the rice root-knot nematode, Meloidogyne graminicola - Galeng-Lawilao, Judith; Kumar, Arvind; De Waele, Dirk (Springer, 2018)
The root-knot nematode Meloidogyne graminicola is an obligate biotrophic pathogen considered to be the most damaging nematode species that causes significant yield losses to upland and rainfed lowland rice production in South and Southeast Asia. Mapping and identification of quantitative trait loci (QTL) for resistance to and tolerance for M. graminicola may offer a safe and economic management option to farmers. In this study, resistance to and tolerance for M. graminicola in Asian rice (Oryza sativa L.) were studied in a mapping population consisting of 300 recombinant inbred lines (RILs) derived from IR78877–208-B-1-2, an aerobic rice genotype with improved resistance to and tolerance for M. graminicola, and IR64, a popular, high-yielding rice mega-variety susceptible to M. graminicola. RILs were phenotyped for resistance and tolerance in the dry seasons of 2012 and 2013. QTL analysis was performed using 131 single nucleotide polymorphism (SNP) and 33 simple sequence repeat (SSR) markers Three QTLs with main effects on chromosomes 4 (qMGR4.1), 7 (qMGR7.1) and 9 (qMGR9.1) and two epistatic interactions (qMGR3.1/ qMGR11.1 and qMGR4.2/ qMGR8.1) associated with nematode reproduction that were consistent in the two seasons were detected. A QTL affecting root galling was found on chromosomes 4 (qGR4.1) and 8 (qGR8.1), and QTLs for nematode tolerance were found on chromosomes 5 (qYR5.1) and 11 (qYR11.1). These QTLs were consistent in both seasons. A QTL for grain yield was found on chromosome 10 (qGYLD10.1), a QTL affecting filled grains per panicle was detected on chromosome 11 (qFG11.1) and a QTL for fresh root weight was found on chromosomes 2 (qFRWt2.1), 8 (qFRWt8.1) and 12 (qFRWt12.1) in both seasons. The donor of the alleles for qMGR4.1, qMGR7.1, qMGR9.1, qGR4.1, qGR8.1, qYR5.1 and qFRWt2.1 was IR78877–208-B-1-2, whereas for qYR11.1, qGYLD10.1 and qFG11.1, qFRWt8.1 and qFRWt12.1 was IR64. Lines having favorable alleles for resistance, tolerance and yield provided better yield under nematode-infested conditions and could be a starting point of marker-assisted breeding (MAB) for the improvement of M. graminicola resistance and tolerance in Asian rice This study identified a total of 12 QTLs with main effects and two epistatic interactions in the 1st season and 2nd season related to M. graminicola resistance and tolerance, and other agronomic traits such as plant yield, percentage of filled grains, and fresh and dry root weight. Rice genotypes that have the favorable alleles for resistance (qMGR4.1, qMGR7.1, qMGR9.1, qGR4.1, qGR8.1) and tolerance (qYR5.1, and qYR11.1,) QTLs, and which are either resistant or partially resistant and tolerant, were also selected. These selected genotypes and the identified QTLs are vital information in designing MAB for the improvement of high-yielding rice genotypes but are susceptible to M. graminicola infection.